REALITAS SOSIAL SEBAGAI DASAR PERTIMBANGAN HAKIM DALAM PUTUSAN PENETAPAN PENGADILAN NEGERI JAKARTA PUSAT NOMOR 155/PDT.P/2023/PN.JKT.PST - Ahmad Fadli Fauzi (Jurnal Yuridis, 2024)
The discourse surrounding interfaith marriage has consistently been a prominent area of legal scholarship in Indonesia. The Indonesian Conference on Religion and Peace (ICRP) indicates that from 2005 to 2023, 1,645 couples who were members of different religious groups were married. This article examines the manner in which social reality serves as the foundation for judges' considerations in the adjudication of applications for interfaith marriages. This article employs a descriptive normative legal research methodology, utilising both a statutory approach and a case approach. This article finds that the social reality in Indonesia is characterised by a high degree of diversity with regard to religion, culture, ethnicity and language, which contributes to the country's distinctive identity, particularly in the context of the special capital city of Jakarta. The Central Jakarta District Court, in its Stipulation Decision (No. 155/Pdt.P/2023/PN.Jkt.Pst), granted the petitioners' request to apply for marriage registration at an authorised institution. In reaching its decision, the judge placed significant emphasis on the social reality of the case as a key factor in determining the legal validity of interfaith marriages. The verdict offers an indirect description of the social reality of Indonesia's plural society, particularly in the context of the Special Capital Region of Jakarta. It is therefore imperative that the issue of interfaith marriages be firmly regulated within the norms of the Marriage Law, in order to prevent the creation of legal vacuums and uncertainty.